POLITICAL PROPAGANDA, MASS MOBILIZATION, AND NARRATIVE OF HABIB RIZIEQ SHIHAB IN THE AKBAR 212 REUNION - Ilham Fariq Maulana (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2020)
This study conducted a study of the rhetorical text of Habib Rizieq Shihab's (HRS) speech at the 212 Grand Reunion in 2019. This research was trying to map the elements of rhetorical motive construction through Burke's Pentadic analysis. However, this research also found gaps in political propaganda by figures and religious groups' leaders with Propaganda Theory. This interpretive research includes five contents of the HRS speech. This study's main conclusion shows that the rhetorical motive is aimed at agent and agency elements that show gaps in political propaganda in mass mobilization nationally and sympathy for HRS religious leaders and acceptance of ideas and ideas in agency elements apolitical political emotions.